PEMBENTUKAN KARAKTER SOSIAL PESERTA DIDIK MELALUI PENDIDIKAN IPS DI ERA MILENIAL - Purwanti, Camelia Istiqomah; Lasmawan, I Wayan; Kertih, I Wayan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education of students' social character through Social Sciences (IPS) education in the millennial era is very important to form individuals who have morality and good social attitudes. In the context of rapid social development, social studies education functions not only as a means of imparting knowledge, but also as a tool for instilling social values ​​such as tolerance, honesty and responsibility. This research aims to explore how social studies education can contribute to the formation of students' social character, as well as the challenges faced in its implementation. Through a literature study approach, this research identifies various methods and strategies used in social studies education to integrate social values. The results show that interactive and collaborative learning, as well as students' involvement in extracurricular activities, can increase their understanding of the importance of social values. Apart from that, the role of teachers as role models in implementing these values ​​also greatly influences students' attitudes. In the millennial era, where social challenges are increasingly complex, social studies education is expected to produce a young generation who is not only academically intelligent but also has strong social character. strong. Thus, social studies education is an important foundation in building a better and more responsible society.